Building Partnerships Between Academic Departments and International Affairs - Butler Cain (Academic Chairpersons Conference Proceedings, 2022)
Department chairs and other campus leaders who have an interest in promoting global awareness in their academic programs should partner with their university’s Office of International Affairs. The worldwide COVID-19 pandemic is causing significant upheaval in international education, so now is an opportune time to begin building strong relationships.
Keywords: International Affairs; Academic Departments; Partnerships